Assessment of Surgical Procedural Time, Pedicle Screw Accuracy, and Clinician Radiation Exposure of a Novel Robotic Navigation System Compared With Conventional Open and Percutaneous Freehand Techniques: A Cadaveric Investigation. Issue 7 (October 2020) - Vaccaro, Alexander R.; Harris, Jonathan A.; Hussain, Mir M.; Wadhwa, Rishi; Chang, Victor W.; Schroerlucke, Samuel R.; Samora, Walter P.; Passias, Peter G.; Patel, Rakesh D.; Panchal, Ripul R.; D'Agostino, Sabino; Whitney, Nathaniel L.; et al.
Study Design: Cadaveric study. Objective: To evaluate accuracy, radiation exposure, and surgical time of a new robotic-assisted navigation (RAN) platform compared with freehand techniques in conventional open and percutaneous procedures. Methods: Ten board-certified surgeons inserted 16 pedicle screws at T10–L5 (n = 40 per technique) in 10 human cadaveric torsos. Pedicle screws were inserted with (1) conventional MIS technique (L2–L5, patient left pedicles), (2) MIS RAN (L2–L5, patient right pedicles), (3) conventional open technique (T10–L1, patient left pedicles), and (4) open RAN (T10–L1, patient right pedicles). Output included (1) operative time, (2) number of fluoroscopic images, and (3) screw accuracy. Results: In the MIS group, compared with the freehand technique, RAN allowed for use of larger screws (diameter: 6.6 ± 0.6 mm vs 6.3 ± 0.5 mm; length: 50.3 ± 4.1 mm vs 46.9 ± 3.5 mm), decreased the number of breaches >2 mm (0 vs 7), fewer fluoroscopic images (0 ± 0 vs 108.3 ± 30.9), and surgical procedure time per screw (3.6 ± 0.4 minutes vs 7.6 ± 2.0 minutes) (all P < .05). Similarly, in the open group, RAN allowed for use of longer screws (46.1 ± 4.1 mm vs 44.0 ± 3.8 mm), decreased the number of breaches >2 mm (0 vs 13), fewer fluoroscopic images (0 ± 0 vs 24.1 ± 25.8) (all P < .05), but increased total surgical procedure time (41.4 ± 8.8 minutes vs 24.7 ± 7.0 minutes, P = .000) while maintaining screw insertion time (3.31.4 minutes vs 3.1 ± 1.0 minutes, P = .650). Conclusion: RAN significantly improved accuracy and decreased radiation exposure in comparison to freehand techniques in both conventional open and percutaneous surgical procedures in cadavers. RAN significantly increased setup time compared with both conventional procedures.